Paucity of CD4+ natural killer T (NKT) lymphocytes in sooty mangabeys is associated with lack of NKT cell depletion after SIV infection. - Namita Rout; James G Else; Simon Yue; Michelle Connole; Mark A Exley; Mark A Exley; Amitinder Kaur (PLoS ONE)
Lack of chronic immune activation in the presence of persistent viremia is a key feature that distinguishes nonpathogenic simian immunodeficiency virus (SIV) infection in natural hosts from pathogenic SIV and HIV infection. To elucidate novel mechanisms downmodulating immune activation in natural hosts of SIV infection, we investigated natural killer T (NKT) lymphocytes in sooty mangabeys. NKT lymphocytes are a potent immunoregulatory arm of the innate immune system that recognize glycolipid antigens presented on the nonpolymorphic MHC-class I-like CD1d molecules. In a cross-sectional analysis of 50 SIV-negative and 50 naturally SIV-infected sooty mangabeys, ligand alpha-galactosylceramide loaded CD1d tetramers co-staining with Valpha24-positive invariant NKT lymphocytes were detected at frequencies >or=0.002% of circulating T lymphocytes in approximately half of the animals. In contrast to published reports in Asian macaques, sooty mangabey NKT lymphocytes consisted of CD8(+) and CD4/CD8 double-negative T lymphocytes that were CXCR3-positive and CCR5-negative suggesting that they trafficked to sites of inflammation without being susceptible to SIV infection. Consistent with these findings, there was no difference in the frequency or phenotype of NKT lymphocytes between SIV-negative and SIV-infected sooty mangabeys. On stimulation with alpha-galactosylceramide loaded on human CD1d molecules, sooty mangabey NKT lymphocytes underwent degranulation and secreted IFN-gamma, TNF-alpha, IL-2, IL-13, and IL-10, indicating the presence of both effector and immunoregulatory functional capabilities. The unique absence of CD4(+) NKT lymphocytes in sooty mangabeys, combined with their IL-10 cytokine-secreting ability and preservation following SIV infection, raises the possibility that NKT lymphocytes might play a role in downmodulating immune activation in SIV-infected sooty mangabeys.